Psychosocial factors influencing treatment adherence in Brazilian gay men living with HIV - Felipe Alckmin-Carvalho; Ângelo Brandelli Costa; Bárbara Giusti; Lucia Yasuko Izumi Nichiata (Revista Portuguesa de Investigação Comportamental e Social)
Context and Aim: Adherence to antiretroviral treatment (ART) among men who have sex with men (MSM) living with HIV poses a public health challenge. Although studies in developed countries emphasize the role of psychosocial factors in ART adherence, there is limited research on this association among Brazilian MSM living with HIV. This study examined the impact of depression, anxiety, internalized homonegativity, and HIV-related stigma on ART adherence in a sample of this population. Method: A cross-sectional study recruited 43 MSM living with HIV (Mage = 34.93, SD = 7.90) through social media. Instruments included sociodemographic and clinical questionnaires, the Questionnaire for Assessment of Adherence to Antiretroviral Treatment, the Beck Depression Scale, the Trait-State Anxiety Inventory, the Internalized Homophobia Scale, and the HIV Stigmatization Scale. Results: Twelve participants (27.9%) showed inadequate ART adherence, and 18 (41.8%) reported signs and symptoms of depression at clinical level. Depression was negatively and moderately correlated with ART adherence. HIV-related stigma was positively and moderately correlated with depression, trait anxiety, and homonegativity. Depression significantly impacted ART adherence, explaining 13.4% of the variance. Conclusions: Our results highlight the need for regular depression screening and affirmative interventions to support MSM living with HIV, addressing stigma, and promoting adherence to ART.